Redox synthesis and high catalytic efficiency of transition-metal nanoparticle-graphene oxide nanocomposites - Wang, Changlong (2017)
Although nanocatalysis is a promising area, increased efficiency and greenness are actively sought. Here we report the principle of the syntheses of graphene oxide (GO)-supported metal nanocatalysts (MNPs) for a variety of transition metals including both noble metals and biometal using either exergonic or endergonic redox reactions between GO and the transition metal salts. These new nanocatalysts are highly efficient in water at ambient temperature for 4-nitrophenol reduction (the test reaction), Sonogashira coupling, azide-alkyne 1,3-cycloaddition (click reaction) and dihydrogen production upon hydrolysis of ammonia-borane and recyclable.